1999
DOI: 10.2166/wst.1999.0486
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Natural Organic Matter (NOM) during Groundwater Recharge using Reclaimed Water

Abstract: The scope of this study was to investigate how natural organic matter (NOM) from drinking water and soluble microbial products (SMP) generated in the wastewater treatment process influence the character of DOC in reclaimed water used for indirect potable reuse. Biodegradation studies in conjunction with XAD-fractionation and 13C-NMR spectroscopy were applied to both characterize organic matter and to study removal mechanisms during subsequent soil-aquifer treatment (SAT). Based on hydraulically corresponding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…Steady infiltration conditions in RBF systems generate a special bioactive filtration layer at the water/sediment interface (Matthess, 1990). Amy et al (1993), Kivimaeki et al (1998), and Drewes and Fox (1999) observed the highest removal of DOC and TOX within the first meter of infiltration. Wang (2002) also reported that the majority of NOM removal occurred within the first 15 m of infiltration.…”
Section: Dissolved Organic Carbonmentioning
confidence: 89%
“…Steady infiltration conditions in RBF systems generate a special bioactive filtration layer at the water/sediment interface (Matthess, 1990). Amy et al (1993), Kivimaeki et al (1998), and Drewes and Fox (1999) observed the highest removal of DOC and TOX within the first meter of infiltration. Wang (2002) also reported that the majority of NOM removal occurred within the first 15 m of infiltration.…”
Section: Dissolved Organic Carbonmentioning
confidence: 89%
“…The ability of the RLS to effectively remove TSS, BOD, and COD at all depths as compared to the sandy and the other soil columns can be attributed to reduced filtration rates thus increasing the residence time for effective filtration and microbial reaction. Infiltration rate has a direct impact on retention time and hence contaminant removal processes with the time defendant behaviour more pronounced up to 1.5 m depth in the vadose zone (Drewes & Fox, 1999). The rare increase in COD concentration in the LS during the five weeks run between 0.3 m and 0.8 m can be attributed to possible short circuiting.…”
Section: Physico-chemical Parameters In Soil Columnsmentioning
confidence: 99%
“…Especially, aerobic microbial activities in the upper layer of soil largely contribute to the removal of DOM during SAT (Drewes and Fox, 1999;Kolehmainen et al, 2007). Meanwhile, there were few researchers focused on DOM removal mechanism, based on the material balances, in the upper layer with active DOM removal.…”
Section: Introductionmentioning
confidence: 99%